Identification of Geometric Patterns in Islamic Art and Architecture of The Abdul Jalil Jatipurno Mosque, Wonogiri - Mahardika, Hafidz; Setyowati, Suryaning; Aji, Fauzi Mizan Prabowo (Sinektika: Jurnal Arsitektur, 2026)
Islam is a religion that not only brings spiritual and social teachings, but also gives birth to unique artistic and architectural traditions. Mosques as centers of worship, education, and social activities are an important medium in expressing Islamic aesthetic values, one of which is through the use of geometric patterns. These patterns are not merely decorative ornaments, but also have philosophical meanings that reflect the principles of order, unity, and eternity in the teachings of monotheism. This study aims to identify and analyze geometric patterns in the architectural elements of the Abdul Jalil Mosque in Jatipurno, Wonogiri Regency. The method used is descriptive qualitative, with data collection techniques in the form of direct observation, documentation, and interviews. The focus of the analysis is directed at the basic geometric forms, symmetry systems, and the aesthetic and symbolic values ​​of the ornaments used. The results show that the dominant geometric pattern is fourfold symmetry, with basic shapes consisting of circles, rectangles, and repeating star patterns. These ornaments are applied consistently to the facade, mihrab, and other structural elements. This research is expected to become a reference in the development of locally based Islamic architecture and support the preservation of the heritage of Islamic ornamental art.